Study on 3D modeling method and reinforcement scheme of large and complex open-pit mine - Tao Zhigang; Ren Shulin; Pang Shihui; Xu Haotian; He Manchao (矿业科学学报, 2021)
Large-scale topping deformation occurred in the southwest stope of Changshanhao Open-pit Gold Mine in Inner Mongolia.Through systematic investigation of the engineering geological conditions and rock mass structure types, the deformation characteristics and failure mechanism of the stope are studied in depth.Taking this project as an example, the 3DMine-FLAC3D large-scale complex geological body high-precision coupling modeling method and modeling process are introduced in detail.Based on this, a slope reinforcement scheme with constant resistance and large deformation anchor cable is proposed, and a numerical simulation method is used to make a comparative study with the original support scheme.The research results show that the geological structure of the southwest stope is complex.Faults and joints are developed.The rock mass in the toppling area is mainly slate and schist with low bending strength, and small deformation anchor cables are used in the supporting structure, which cannot resist large slope deformation.The combined effect of these factors leads to the occurrence of dumping instability.The reinforcement scheme to constant-resistance and large-deformation anchor cables can effectively control the slope deformation and a better support effect is obtained.